(untitled) (Agronomy Journal of Nepal, 2021)
A field experiment was conducted to evaluate the effect of tillage and nutrient management practices on the performance of subsequent wheat and maize in the rice-based cropping system at Agriculture and Forestry University (AFU), Rampur, Chitwan, Nepal during November 2018-May 2019. The experiment was executed in a split-plot for evaluating two establishment methods viz. (i) zero tillage followed after (fa) conventionally tilled dry direct seeded rice ( ZT fa CT-DDSR) (ii) conventional tillage followed after puddled transplanted rice (CT fa Pu-TPR) and four nutrient management practices, i.e. (i) recommended dose (100% RDF; 80:60:40 and 180:90:60 N:P2O5:K2O kg/ha for wheat and maize respectively), (ii) Residue retention of rice crop @ 5 t/ha + 75% RDF (RR +75% RDF), (iii) Nutrient expert (NE) dose (140:60:45; 150:50:90 N:P2O5:K2O kg/ha for wheat and maize respectively), (iv) Rice residue @ 3.5 t/ha +75% RDF of each crop followed after brown/green manuring of Sesbania in rice (R+75% RDF fa BM/GM) and the treatments were replicated thrice. The data on yield (rice equivalent yield), yield attributes, and economics were recorded and analyzed by R studio. The study revealed that none of the yield attributes and rice equivalent yield of wheat were significantly influenced by the tillage methods but maize had significantly higher number of grains per cob under CT fa Pu-TPR and significantly higher (8.9%) yield under ZT fa CT-DDSR. NE assisted nutrient management practice produced significantly a greater number of spike (281.9 per m2 ) and grains per spike (44.5 and higher straw yield (5.9 t/ha) for wheat crop and also showed better performance for maize as well. Maize had yield advantage of 21% and 14% when planted after BM/GM practices in rice and residue mulched condition respectively. The rice equivalent yield of wheat was 21% and 16% more under NE dose and R+75% RDF fa BM/GM respectively compared to 100% RDF. NE dose was the most profitable in terms of B:C ratio for both the wheat (1.9) and maize (3.0). Hence, tillage methods were indifferent for wheat but ZT fa CT-DDSR was significantly productive for maize and NE dose was the best nutrient management practice for better productivity and profitability for the wheat and maize in the rice-based cropping system in inner Terai of Nepal.